2016
DOI: 10.1007/s00125-016-4067-4
|View full text |Cite
|
Sign up to set email alerts
|

Islet cell hyperexpression of HLA class I antigens: a defining feature in type 1 diabetes

Abstract: Aims/hypothesis Human pancreatic beta cells may be complicit in their own demise in type 1 diabetes, but how this occurs remains unclear. One potentially contributing factor is hyperexpression of HLA class I antigens. This was first described approximately 30 years ago, but has never been fully characterised and was recently challenged as artefactual. Therefore, we investigated HLA class I expression at the protein and RNA levels in pancreases from three cohorts of patients with type 1 diabetes. The principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
240
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(264 citation statements)
references
References 42 publications
22
240
0
2
Order By: Relevance
“…This observation was confirmed with various methodologies in multiple patient cohorts (26) (Figure 2). Hyperexpression of HLA-I molecules helps explain the predominance of CD8 + T cells in insulitis.…”
Section: T Cells In the Prediabetic Pancreassupporting
confidence: 69%
“…This observation was confirmed with various methodologies in multiple patient cohorts (26) (Figure 2). Hyperexpression of HLA-I molecules helps explain the predominance of CD8 + T cells in insulitis.…”
Section: T Cells In the Prediabetic Pancreassupporting
confidence: 69%
“…Our present data, however, suggest that the roles of STAT1 and STAT2 are not redundant in beta cells, as the observed increase in STAT1 activation is not sufficient to compensate for the lack of STAT2. A very recent study has shown that HLA hyperexpression is strongly correlated with STAT1 expression in beta cellcontaining islets from type 1 diabetes patients [1]. STAT2 was not investigated in this study.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, histological analysis and other approaches have identified higher expression of type I IFNs in islets from patients with type 1 diabetes [7][8][9][10], and self-reactive antibodies targeting type I IFNs are associated with protection against type 1 diabetes in patients with an autoimmune syndrome [20]. Three hallmarks of the pancreatic islets in early human type 1 diabetes are overexpression of HLA class I [1,2], ER stress [3,37] and beta cell apoptosis [6], and we presently show that IFNα induces or contributes to these three phenomena in human beta cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular heterogeneity of B cells infiltrating the islets can be correlated with β-cell destruction, insulin-containing islets, and age of onset of T1D [38,40 ▪ ]. Interestingly, the hyperexpression of Human Leukocyte Antigen (HLA) Class I by pancreatic β cells [26,39,41,42 ▪ ,43] is associated with T1D, but can be heterogeneous in expression; this was seen as well even in those individuals with serum autoantibody, but without a clinical diagnosis of T1D [44]. However, the role of hyperexpression of HLA class I in T1D pathology remains under investigation.…”
Section: Islet-infiltrating T Cells: Histological and Immunohistologimentioning
confidence: 99%